Phytochemical Analysis and Antibacterial Activities of Cymbopogon citratus from Banke, Nepal - Magar, Bhuwan Budha; Rai, Nelson; Shrestha, Manish Man; Shahi, Ikcha; Bhatt , Bishan Datt (Orchid Academia Siraha, 2024)
Plant extracts are being used in the development of antibacterial agents because they offer promising sources of new and effective antibacterial compounds. This study aimed to investigate the phytochemical composition and antibacterial properties of the methanolic extract of Cymbopogon citratus, commonly known as "Kagate Ghas" (कागते घाँस). Freshly harvested and shade-dried leaves of Cymbopogon citratus were subjected to methanolic extraction using a Soxhlet apparatus. The extract was tested for its natural chemical compounds and was found to contain alkaloids, flavonoids, glycosides, tannins, saponins, terpenoids, proteins, and carbohydrates. Interestingly, steroids were not detected in the analysis. The disc diffusion method was used for the assessment of antibacterial activity against gram-positive Bacillus subtilis (ATCC 6051) and the gram-negative Enterobacter aerogenes (ATCC 29007), with a zone of inhibition (ZOI) measuring 12 mm against B. subtilis and 7 mm against E. aerogenes. This indicates methanolic extract of C. citratus is more effective against gram-positive than gram-negative bacteria.